RESEPSI MASYARAKAT TERHADAP MUSHAF KUNO TEMBARUK DI DESA SAJANG KECAMATAN SEMBALUN, NTB: LIVING QUR’AN - Hamzah Fansyuri (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2023)
With the advancement of technology that prints tens of thousands of printed mushaf every day, the product of technological progress is not able to replace the role of ancient mushaf completely, especially in the rituals that are commonly carried out in the community of Sajang Village. Ancient mushaf had a duality of values; its value as the Word of God and as an ancestral inheritance. Therefore, the way of respect is also different from the way of respecting mushaf in general. This research uncovered the way and model of respect by taking these words and behaviors that were poured out by writing and taking pictures that are considered important and useful. This type of research is qualitative research that focused research on people's methods of intercepting verses of the Qur'an. Furthermore, the reality of mushaf reverence in the midst of traditional society was researched using the approach of reception and living Quran in looking at the symptoms that encourage local people who still maintain ancient mushaf reverence rituals amid the currents of modernity. After going through the research steps, the author managed to find some conclusions: (1) The People of Sajang Village respect the ancient mushaf Tembaruk in various ways, meaning that there is a different way of respect between ancient mushaf and printed mushaf. (2) The background of the people of Sajang Village in honoring ancient mushaf because of their concern for parents who are considered wise and must be maintained. In addition to ancestral orders, respect for mushaf is also done in order to avoid the misery of life (bahla). (3) The reception of reverence for the ancient mushaf lies in the influences of the subconscious.